The influence of fire presence and absence on grass species composition and species richness at Mountain Zebra National Park - Nthabe Munyai; Abel Ramoelo; Samuel Adelabu; Hugo Bezuidenhout (Koedoe: African Protected Area Conservation and Science, 2023)
It is well known that fire is a common driver in many biomes and it plays a vital role in maintaining ecosystem functioning in many South African biomes. This ecosystem process is an important determinant of plant community composition and diversity, and can result in changes in structural composition and ecosystem functioning. The main objectives of this study are to determine the influence of fire on grass species richness, diversity and composition in Mountain Zebra National Park. Using satellite imagery, the park’s fire history was determined between 2000 and 2020. Eighty plots (approximately 20 m × 20 m; 100 m apart) were laid out purposively across different fire regimes. There was no significant difference in both species richness and diversity in burned and unburned sites. However, there was a difference in species composition between burned and unburned sites and between different fire frequencies. The unburned site had higher moribund material and unpalatable grasses compared to the burned area.